Innovative Teaching Strategies and Performance of Agriculture Subject in Uganda’s Secondary Schools: A Case Study of Kabale Municipality. - Byomuhangi, Nelson (Kabale University, 2024)
The aim of this study was to make an evaluation of the effect of innovative teaching Strategies on the performance of Agriculture Subjects in secondary schools in Kabale municipality. The study was descriptive in nature with a blend of both quantitative and qualitative approaches. The study sampled 81 respondents including headteachers, deputy headteachers, teachers from both private and government secondary schools, and 1 education officer. Primary data was collected using a self-administered questionnaire and interview guide while secondary data was collected using documentary review. The major findings indicated that secondary schools that taught agriculture in Kabale municipality taught theoretical lessons using lecture methods whenever it came to class work and for experiments, they had laboratories whereas for the practical part, they had field tours mainly for candidate classes. This was represented by the mean=4.75, std. dev= .434. The study revealed that out of the strategies such as tours and trips, the use of demonstrations in class and transferring theory into practice made the learning of agriculture subjects attractive and interesting for learners. Further, the study revealed that with the use of innovative teaching strategies, there was a positive significant effect on the grades of learners as schools had registered significant performance in the subject that was derived from the learning and teaching using lectures, demonstrations, and field practical work (df= 4, 72, F=10.921, P=.000). The study recommended that Policymakers such as the ministry of education and sports need include the program of innovative teaching strategies on the national curriculum.